ATTITUDES TOWARDS TEACHERS’ CODE-SWITCHING IN GEORGIAN EDUCATIONAL DISCOURSE - Buskivadze, Khatuna (Online Journal of Humanities ETAGTSU, 2021)
Based upon the theories of sociolinguistics, the article examines students’ and teachers’ attitudes towards teachers’ code choice and analyses the features and functions of teachers’ code- switching (CS) in the context of the Georgian educational discourse (practice research, teaching English for specific purposes (ESP). The article presents the results of quantitative research. The study of teachers’ code- switching in the ESP classroom reveals that code switching is extensively employed by business English teachers. Teachers, as well as students, have a negative attitude towards teachers using L1 in Business English classes. CS is positively encouraged by less than a half of the students surveyed. Full Text (PDF)